The other valley : a novel - Howard, Scott Alexander (Atria Books, 2024)
"Set in an unnamed valley-surrounded by other valleys, each twenty years apart in time-a masterful, moving literary speculative novel in which the Conseil determines if a bereaved resident can cross the border to the past or the future on a "mourning tour." One sixteen-year-old Conseil candidate spots two visitors from the future, but is shocked when she recognizes them as the parents of the boy she loves"--